Adherens junctions: from molecules to morphogenesis - Harris, Tony J. C.; Tepass, Ulrich (Nature reviews. Molecular cell biology, 2010)
Key Points Adherens junctions (AJs) meet the dual challenge of maintaining tissue architecture and facilitating cell movement during tissue development and renewal. Across animal species, classic cadherins display diversity in the structure of their extracellular regions but share a conserved cytoplasmic tail and a common tendency to form clusters at the plasma membrane. The cytoplasmic tail of classic cadherin binds to the catenins, which mediate links to cytoskeletal networks as well as exocytotic and endocytic machinery. Crosstalk between cadherin–catenin clusters and actin regulators directs AJ assembly from initial cell–cell contacts. Links between cadherin–catenin clusters and microtubules organize epithelial cells more globally. Regulated endocytosis of cadherin–catenin clusters facilitates AJ remodelling. The effects of cytoskeletal or endocytic regulation of AJs on overall tissue structure depends on whether the regulation occurs locally, at a subset of cell–cell contacts of individual cells, or globally, at all cell–cell contacts. Recent work has advanced our understanding of the molecular organization of adherens junctions and how cadherin–catenin complexes at their core engage actin, microtubules and the endocytic machinery. This provides insight into how adherens junctions can maintain tissue architecture and facilitate cell movement during tissue morphogenesis. How adhesive interactions between cells generate and maintain animal tissue structure remains one of the most challenging and long-standing questions in cell and developmental biology. Adherens junctions (AJs) and the cadherin–catenin complexes at their core are therefore the subjects of intense research. Recent work has greatly advanced our understanding of the molecular organization of AJs and how cadherin–catenin complexes engage actin, microtubules and the endocytic machinery. As a result, we have gained important insights into the molecular mechanisms of tissue morphogenesis.